Mixed convection flow over a slender cylinder due to the combined effects of thermal and mass diffusion. (2016) - Anilkumar, Devarapu; Datta, Prabal; Pandey, Bishun D.
This paper deals with the similarity solution of double-diffusive mixed convection flow over a vertical slender cylinder due to the combined effects of thermal and mass diffusion. Local similarity method has been used to transform governing nonlinear partial differential equations into ordinary differential equations. With the help of a set of suitable similarity transformations, the nonlinear coupled partial differential equations governing select phenomena (such as flow, thermal and concentration field) have been reduced to a set of nonlinear coupled ordinary differential equations. Numerical solution of system of nonlinear ordinary differential equations are derived using an implicit finite difference scheme along with quasilinearisation technique. The significant observations of the study are as follows: 1) strong effect of buoyancy parameter λ on the flow and thermal field; 2) strong influence of Prandtl number (Pr) and Sherwood number (Sc) on heat transfer and mass transfer respectively.